Analisis Perbandingan Penyimpanan Data Rekam Medis Elektronik berstandar FHIR pada Sistem Basis Data: BigchainDB, MySQL dan MongoDB - Danang Kastowo; Suwanto Raharjo (Lentera Dua Indonesia, 2023)
The availability of medical record data can affect the health services that will be provided, starting from treatment planning, therapy, and health facilities provided to patients. The integrity of electronic medical record data needs to be maintained, a method that can be used by implementing a decentralized database system, namely implementing blockchain technology. In addition to data integrity, data standardization also needs to be carried out in the health area, in order to facilitate the integration process with other systems. The international data standard that can be used is FHIR (Fast Healthcare Interoperability Resources). FHIR has great potential to be developed in Indonesia because several hospitals in Indonesia already have a health system and electronic medical record data. BigchainDB and FHIR can be combined to store electronic medical record data, the results of this study by implementing both, the BigchainDB database system requires a long processing time, when compared to MongoDB and MySQL, but for reading medical record data it is not much different from MongoDB. The most effective and efficient MongoDB database for storing and reading medical record data is the FHIR scheme, but this database needs to be configured more deeply in order to get decentralized features like BigchainDB. MySQL has faster data storage capabilities when compared to BigchainDB, but for data reading and the need for a replication scheme to get features such as decentralization, a more in-depth configuration is needed.